ChemInform Abstract: Fundamental Pd0/PdII Redox Steps in Cross‐Coupling Reactions: Homogeneous, Hybrid Homogeneous‐Heterogeneous to Heterogeneous Mechanistic Pathways for C—C Couplings. Issue 38 (10th September 2014) - Fairlamb, Ian J. S.; Lee, Adam F.
Abstract Review: 114 refs.